Mutually exclusive BCOR internal tandem duplications and YWHAE‐NUTM2 fusions in clear cell sarcoma of kidney: not the full story. Issue 5 (April 2016) - Kenny, Colin; Bausenwein, Sabrina; Lazaro, Antonio; Furtwängler, Rhoikos; Gooskens, Saskia LM; van den Heuvel Eibrink, Marry; Vokuhl, Christian; Leuschner, Ivo; Graf, Norbert; Gessler, Manfred; O'Sullivan, Maureen J
Abstract: Internal tandem duplication within the BCOR gene sequence that encodes the PUFD domain, important in the formation of the non‐canonical or variant polycomb repressor complex 1 (v‐PRC1), was very recently described in 100% of 20 clear cell sarcomas of kidney (CCSKs). None of those 20 cases bore the YWHAE–NUTM2 transcript, previously described by us in CCSK, and which constitutes the only other recurrent genetic aberration observed in CCSK, prompting consideration that these mutations might be mutually exclusive in CCSK. We analysed a cohort of 159 CCSKs and can now not only confirm that there is indeed mutual exclusivity of these BCOR and YWHAE mutations, but also show that a substantial proportion (in this series 11.8%) of CCSKs bear neither mutation when tested by these assays, raising the possibility of distinct aetiologies for subsets of CCSK. Clinical differences observed between the subsets support this notion. As CCSK may show poor chemo‐responsiveness, and current treatment protocols mandate the use of doxorubicin with its associated side‐effects, advances in understanding the disease biology with a view to more targeted and personalized treatment is a pressing need. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.